PENGGUNAAN MEDIA VIDEO ANIMASI TERHADAP KETERAMPILAN MENYIMAK KELAS V SD NEGERI 90 PALEMBANG - Syahida; Hetilaniar; Dina Sri Nindiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Listening skills are an essential component in language learning, particularly for elementary school students who are still in the stage of developing basic language abilities. However, in many learning settings, listening activities are often delivered conventionally, which tends to be less engaging and less effective. This study aims to determine the effect of using animated video media on the listening skills of fifth-grade students at SD Negeri 90 Palembang in the context of learning folk tales. The research method used is a quasi-experimental design with a nonequivalent control group design. The study involved two classes: one experimental class taught using animated video media and one control class taught using conventional methods. Data were collected through pretest and posttest using essay-type listening comprehension questions. The results of the study show that students taught with animated video media demonstrate higher improvement in their listening skills compared to those taught conventionally. The use of animated videos provides a more interactive and enjoyable learning experience, increasing students’ focus and comprehension. Based on the hypothesis test, there is a significant difference in the listening skills outcomes between the two groups, indicating that animated video media has a positive and effective impact on students' listening abilities. Therefore, animated videos can be considered as an innovative and effective alternative learning medium in improving listening skills in elementary education.